Impact of Facebook Addiction Behavior on Self-Esteem Among Working-Age Hospital Personnel - Wangkiat, Pawaris (Journal of Primary Care and Family Medicine (PCFM), 2024)
Background and Objectives: Facebook addiction affects self-esteem, especially among adolescents and students. However, there is limited information on the impact of Facebook addiction on adults or the working population. This study studied the prevalence of Facebook addiction and its relationship to self-esteem among hospital personnel. Design: A cross-sectional study Materials and Methods: The data were collected from personnel in a central hospital in Southern Thailand, from June to November 2021, by stratified random sampling. Online questionnaires were used to collect data, including the Bergen Facebook Addiction Behavior Questionnaire and the Revised Thai RSES Self-Esteem Scale. Multiple logistic regression method was used to analyze the data through the Stata/IC 16 program. Results: Six hundred eighty-eight personnel in the hospital responded to the questionnaire, with 74 males (10.8%) and 614 females (89.6%). The average age was 38.43 ± 10.03 years old. The prevalence of Facebook addiction was 99 cases (14.4%). In terms of self-esteem, 84 cases (12.2%) were identified as having low self-esteem; 487 cases (70.8%) had a middle level of self-esteem, and high self-esteem was identified in 117 cases (17.0%) There was a statistical significant correlation between low self-esteem and Facebook addiction (adj. OR = 1.97, 95% CI: 1.09-3.58), as well as educational level. bachelor’s degree or higher qualification (adj. OR. = 0.47, 95% CI: 0.26-0.85). Conclusions: Facebook addiction behavior among working-age personnel in hospitals is a key factor in their low self-esteem. This is consistent with previous studies in adolescents and students. Therefore, preventing social media addiction behavior is important.